A new cemented hip prosthesis concept - Ramos, António (2011)
The orthopedic market offers more than 200 hundred different femoral stems, some with scientific published results. The influence of stem geometry relatively to stress distribution on the cement mantle has been addressed by some authors. Stem geometry influences the fatigue mechanism process at the stem-cement interface and may cause aseptic loosening. This study presents a new cemented hip femoral concept. The study was based on finite element analysis and in vitro hip replacements. The numerical models allowed us to determine the cement mantle stresses of commercial stems that were compared with the ones of the new concept. The stem developed presents innovative collar and tip geometries and "organic" stem sections. The new cemented hip prosthesis reduces the average cement stresses .around 25% relatively to the best commercial stems studied.